POLYSACCHARIDES TUSSILAGOFARFARA L. REDUCE MYELOSUPPRESSION INDUCED BY CISPLATIN AND ETOPOSIDE - E. A. Safonova (Sibirskij Onkologičeskij Žurnal, 2017)
The purpose of the study was to investigate the influence of polysaccharides Tussilagofarfara L. on erythroid sprout hematopoiesis, tumor growth and metastasis in mice with Lung cancer-67 during therapy with cisplatin and etoposide. It was found that the use of polysaccharides reduces myelosuppression induced by cytostatics of erythroidal sprout hematopoiesis and leads to increase anti-tumor and anti-metastatic effect of chemotherapy.